A positive electrode material and preparation method thereof and lithium ion battery

By adopting a double-layer cladding structure of lithium-rich disordered materials and layered bimetal oxides in the positive electrode materials, the challenges of existing positive electrode materials in terms of high energy density and long cycle life are solved, and higher thermal stability, rate performance and cycle performance are achieved.

CN119050346BActive Publication Date: 2025-03-11JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411515647.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-11
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing nickel-rich nickel-cobalt-manganese cathode materials have challenges in high energy density and long cycle life, including cation mixing, surface side reaction of electrode materials, dissolution of transition metals and hydrofluoric acid reactions, and microcracks inside and between grains.

Method used

The positive electrode material adopts a double-layer clad structure, the inner layer is a lithium-rich disorder material and a positive electrode matrix material, and the outer layer is a layered bimetal oxide. This structure improves the thermal stability, rate performance and cycling performance of the material through the collapsing substance and the coating sequence.

Benefits of technology

The rapid deembossing of lithium ions is achieved, the structural stability and specific surface area of ​​the material are improved, the internal resistance of the battery is reduced, and the chemical corrosion resistance and safety are enhanced, thereby improving the thermal stability, rate performance and cycling performance of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119050346B_ABST
    Figure CN119050346B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode material, a preparation method thereof and a lithium ion battery. The positive electrode material comprises a core, a first coating layer and a second coating layer from the inside to the outside; the core comprises a positive electrode matrix material; the first coating layer comprises a lithium-rich disordered material; and the second coating layer comprises a layered bimetallic oxide. The positive electrode material provided by the present invention improves the thermal stability, rate performance and cycle performance of the positive electrode material through the synergistic coordination of the coating materials of the first coating layer and the second coating layer and the coating sequence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a positive electrode material and a preparation method thereof and a lithium ion battery. Background Art

[0002] While technological innovation is going on, there is a more urgent need for rechargeable lithium-ion batteries with high energy density, which further promotes the development of high specific capacity electrode materials. The lower limit of the energy density of lithium-ion batteries depends on the positive electrode material. Nickel-rich layered transition metal oxides have attracted the attention of academia and industry for their superior performance over other positive electrode materials. Among the layered multi-element materials, NCM111-type low-nickel materials are the earliest proposed material composition, in which transition metal elements such as Ni, Co, and Mn have the same composition ratio, and have the performance advantages of high rate, long cycle and high safety. Based on the demand for higher specific capacity, NCM424, NCM523, NCM622, NCM712 and NCM811 are gradually introduced to the market to meet the needs of various segmented application markets in multiple fields such as power tools, hybrid electric vehicles, and pure electric vehicles. While improving the specific capacity, nickel-rich nickel-cobalt-manganese positive electrode materials also face some problems and challenges that lead to capacity decay. The main problems include: 1) cation mixing, which leads to crystal structure transformation; 2) oxygen and carbon dioxide are released from the surface of electrode materials, which produce side reactions with the electrolyte; 3) transition metals react and dissolve with hydrofluoric acid; 4) microcracks are easily generated inside and between grains after long cycles and under high charge conditions.

[0003] To address the existing problems, the commonly used improvement methods currently include: 1) trying new methods for synthesizing ternary high-nickel materials to avoid side reactions caused by traditional methods (such as co-precipitation); 2) constructing single crystal particles; 3) introducing other anions and cations to stabilize the material structure; 4) coating the material surface to prevent side reactions.

[0004] Although new synthesis processes, structural modifications, ion doping and coating can optimize performance, it is still impossible to completely avoid the occurrence of surface side reactions. Conventional oxides, such as Al 2 O 3 , TiO 2 , ZrO 2 etc., which can slow down the reaction between the electrode material surface and the electrolyte, but will increase the surface impedance of the material and fail to balance the electrical performance and structural stability. 3 Fluoride and lithium-rich layered oxide are co-coated on the surface of the ternary positive electrode material to improve chemical stability and capacity, but this method is not suitable for mass preparation of electrode materials, and fluoride has some defects, such as easy to cause fluoride poisoning and the coating layer will reduce the diffusion rate of lithium ions.

[0005] Therefore, how to improve the cycle and rate performance of positive electrode materials while achieving high energy density is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a positive electrode material and a preparation method thereof and a lithium ion battery. The positive electrode material provided by the present invention improves the thermal stability, rate performance and cycle performance of the positive electrode material through the synergistic coordination of the coating materials of the first coating layer and the second coating layer and the coating sequence.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a positive electrode material, which comprises, from inside to outside, a core, a first coating layer, and a second coating layer;

[0009] The inner core includes a positive electrode matrix material; the first coating layer includes a lithium-rich disordered material; and the second coating layer includes a layered bimetallic oxide.

[0010] The positive electrode material provided by the present invention, the coating materials of the first coating layer and the second coating layer, and the coating sequence cooperate with each other to jointly coat and modify the positive electrode matrix material, which is conducive to the rapid release of a large number of lithium ions. The lithium-rich disordered material will form a percolation network in the lithium-rich state, open new ion migration channels, accelerate the migration of lithium ions, and effectively improve the structural stability of the material. The layered bimetallic oxide coating layer can effectively reduce the side reactions generated with the electrolyte, etc., and also increase the specific surface area of ​​the material, reduce the contact impedance between the outer coating layer and the core material, reduce the internal resistance of the battery, and can also absorb part of the oxygen released by the positive electrode material to improve safety, thereby improving the thermal stability, rate performance and cycle performance of the positive electrode material.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] Preferably, the lithium-rich disordered material is a rock salt structure material.

[0013] Preferably, the chemical formula of the lithium-rich disordered material is Li a TM 2-a O 2 , 1≤a<2, TM is a transition metal element.

[0014] Preferably, the D50 of the lithium-rich disordered material is 50nm~300nm.

[0015] Preferably, the mass of the first coating layer is 0.5% to 1.5% of the mass of the core.

[0016] Preferably, the layered bimetallic oxide is a lamellar structure, and the thickness of the lamellar structure is 2nm~20nm.

[0017] Preferably, the layered bimetallic oxide includes a divalent metal element A and a trivalent metal element B, the divalent metal element A includes at least one of Mg, Co, Ni, Zn or Cu, and the trivalent metal element B includes at least one of Al, Cr, Fe or Ga.

[0018] Preferably, the mass of the second coating layer is 0.5% to 2% of the sum of the masses of the core and the first coating layer.

[0019] Preferably, based on the total molar amount of all metal elements in the positive electrode matrix material being 100%, the molar amount of nickel in the positive electrode matrix material accounts for ≥50%.

[0020] Preferably, the chemical formula of the positive electrode matrix material is LiNi x Co y M 1-x-y O 2 , wherein M includes Mn and / or Al, x≥0.5, y≥0, 1-xy>0.

[0021] Preferably, the layered bimetallic oxide includes divalent metal elements and trivalent metal elements, and the positive electrode matrix material is also doped with the trivalent metal elements in the layered bimetallic oxide.

[0022] In a second aspect, the present invention provides a method for preparing the positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0023] first mixing the positive electrode matrix material and the lithium-rich disordered material, and performing a first sintering on the first mixed material to obtain an intermediate material;

[0024] The intermediate material and the layered double metal hydroxide material are mixed in a second manner, and the second mixed material is subjected to a second sintering to obtain the positive electrode material.

[0025] Preferably, the sintering temperature of the first sintering is 700° C. to 900° C., and the sintering time of the first sintering is 4 h to 8 h.

[0026] Preferably, the sintering temperature of the second sintering is 400° C. to 650° C., and the sintering time of the second sintering is 2 h to 4 h.

[0027] Preferably, the chemical formula of the layered double metal hydroxide is [A2+ 1-x1 B 3+ x1 (OH) 2 ] (C n- ) x1 / n ·zH 2 O, 0.2≤x1≤0.4, n>0, z>0.

[0028] Preferably, A is a divalent metal element, and the divalent metal element includes at least one of Mg, Co, Ni, Zn or Cu.

[0029] Preferably, B is a trivalent metal element, and the trivalent metal element includes at least one of Al, Cr, Fe or Ga.

[0030] Preferably, the C n- is an interlayer anion, wherein the interlayer anion includes NO - , Cl - OH - 、SO 4 2- ,PO 4 - , C 6 H 4 (COO) 2 2- At least one of .

[0031] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the positive electrode material as described in the first aspect or the positive electrode material prepared by the preparation method as described in the second aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The positive electrode material provided by the present invention cooperates with the coating materials of the first coating layer and the second coating layer and the coating sequence to jointly coat and modify the positive electrode base material, which can realize the rapid deintercalation of lithium ions. The lithium-rich disordered material in the first coating layer has a high lithium threshold and can form a percolation network, open a new ion migration channel 0-TM, accelerate migration and diffusion, improve rate performance, and can also reduce the alkali content and stabilize the structure on the surface of the positive electrode base material; the layered bimetallic oxide in the second coating layer provides a large amount of open space, which increases the specific surface area of ​​the material while providing surface protection, can absorb part of the oxygen released by the positive electrode, improve the thermal stability of the positive electrode material, reduce the internal resistance of the battery, and inhibit the dissolution of the electrode material and the cracking of the secondary particle surface; at the same time, the double-layer coating makes the material show good chemical corrosion resistance, and reduces the problems of agglomeration and sintering of nanoparticles, thereby improving the thermal stability, rate performance and cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the XRD pattern of NiAl-LDHs provided in Example 1.

[0035] Figure 2 This is the XRD diagram of the positive electrode material provided in Example 1.

[0036] Figure 3 This is the SEM image of NiAl-LDHs provided in Example 1.

[0037] Figure 4 The positive electrode matrix material LiNi provided in Example 1 0.8 Co 0.1 Mn 0.1 O 2 SEM image of . DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0040] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0041] In a specific embodiment, the present invention provides a positive electrode material, which includes a core, a first coating layer and a second coating layer from the inside to the outside;

[0042] The inner core includes a positive electrode matrix material; the first coating layer includes a lithium-rich disordered material; and the second coating layer includes a layered bimetallic oxide.

[0043] The positive electrode material provided by the present invention, the coating materials of the first coating layer and the second coating layer and the coating sequence cooperate with each other to jointly coat and modify the positive electrode base material, which can realize the rapid deintercalation of lithium ions. The lithium-rich disordered material in the first coating layer has a high lithium threshold and can form a percolation network, open a new ion migration channel-a non-coplanar transition metal cation diffusion channel (0-TM), accelerate migration and diffusion, improve rate performance, and reduce the alkali content and stable structure on the surface of the positive electrode base material; the layered bimetallic oxide in the second coating layer provides a large amount of open space, which increases the specific surface area of ​​the material while providing surface protection, can absorb part of the oxygen released by the positive electrode, improve the thermal stability of the positive electrode material, reduce the internal resistance of the battery, and inhibit the dissolution of the electrode material and the cracking of the secondary particle surface; at the same time, the double-layer coating makes the material show good chemical corrosion resistance, and reduces the problems of agglomeration and sintering of nanoparticles, thereby improving the thermal stability, rate performance and cycle performance of the positive electrode material.

[0044] In the present invention, the type of coating material and the coating sequence are indispensable and work together. If the coating sequence is changed, the gradient concentration required for lithium ion diffusion cannot be formed. At the same time, after a long cycle, the surface lithium-rich disordered material structure will collapse, and it will produce side reactions with the electrolyte, aggravating the decline of battery performance. As a preferred technical solution in a specific implementation, the lithium-rich disordered material is a rock salt structure material.

[0045] In the present invention, the lithium-rich disordered material is a rock salt structure, which can better improve the concentration of active lithium ions and obtain a lithium ion migration channel with lower impedance.

[0046] As a preferred technical solution in a specific embodiment, the chemical formula of the lithium-rich disordered material is Li a TM 2-a O 2 , 1≤a<2, for example 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, TM is a transition metal element, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In the present invention, in the lithium-rich disordered material, the disordered rock salt Li-TM oxide with excess lithium can provide a higher capacity, which is attributed to the diffusion of the 0-TM channel, which promotes the diffusion of Li in the disordered rock salt positive electrode, wherein the value range of 1≤a≤1.2 is adjusted to better form the 0-TM channel, thereby promoting the migration of lithium ions; and the present invention does not specifically limit the specific element type of TM, and the lithium-rich disordered material can be obtained, and the transition metal element type of the rock salt structure is applicable to the present invention, for example, the TM includes but is not limited to at least one of Ni, Ti, Nb, Mn, Cr, Mo or V; further, when Mo and Cr are selected as TM elements in the lithium-rich disordered material (such as Li 1.2 Mo 0.5 Cr 0.3 O 2 ), which is more conducive to improving structural stability and material capacity. The valence of Mo and Cr contains some +6, and the proportion can be lower than that of +5 elements. During the charge and discharge process, the valence of Mo and Cr is more stable and will not change.

[0048] It should also be noted that the preparation method of the lithium-rich disordered material provided by the present invention is a conventional technical solution, and those skilled in the art can directly obtain the corresponding product structure, or prepare it by themselves using a conventional preparation process.

[0049] As a preferred technical solution in a specific embodiment, the D50 of the lithium-rich disordered material is 50nm~300nm, for example 50nm, 75nm, 100nm, 125nm, 150nm, 175nm, 200nm, 225nm, 250nm, 275nm or 300nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In the present invention, the D50 of the lithium-rich disordered material is adjusted to 50nm~300nm, further realizing short-distance ion migration.

[0051] As a preferred technical solution in a specific embodiment, the mass of the first coating layer is 0.5% to 1.5% of the mass of the inner core, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In the present invention, the mass of the first coating layer is 0.5% to 1.5% of the mass of the core, so that a coating layer structure uniformly coated on the surface of the positive electrode substrate material can be obtained, which provides sufficient channels for the migration of lithium ions and avoids excessive coating, which will lead to a decrease in the migration rate of lithium ions and make it difficult to support the improvement of long-cycle performance.

[0053] As a preferred technical solution in a specific embodiment, the layered bimetallic oxide is a lamellar structure, and the thickness of the lamellar structure is 2nm~20nm, for example 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In the present invention, the layered bimetallic oxides with a lamellar structure are interlaced in the second coating layer to form a flower-like structure, thereby providing more development space, obtaining a larger specific surface area, and better reducing the internal resistance of the battery; and further adjusting the thickness of the lamellar structure to 2nm~20nm, forming an ultra-thin structure, and also shortening the migration path of holes to the surface, which is beneficial to the migration of lithium ions.

[0055] As a preferred technical solution in a specific embodiment, the layered bimetallic oxide includes a divalent metal element A and a trivalent metal element B, the divalent metal element A includes at least one of Mg, Co, Ni, Zn or Cu, and the trivalent metal element B includes at least one of Al, Cr, Fe or Ga.

[0056] As a preferred technical solution in a specific implementation, the mass of the second coating layer is 0.5% to 2% of the sum of the masses of the inner core and the first coating layer, for example 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In the present invention, the mass of the second coating layer is 0.5% to 2% of the sum of the masses of the core and the first coating layer. If the coating amount is too low, a large exposed area will be formed, and side reactions with the electrolyte and the like cannot be avoided. If the coating amount is too high and the coating is thick, the diffusion of lithium during the insertion and extraction process will be hindered, thereby affecting the rate performance.

[0058] As a preferred technical solution in a specific embodiment, taking the total molar amount of all metal elements in the positive electrode matrix material as 100%, the molar amount of nickel in the positive electrode matrix material accounts for ≥50%, for example 50%, 53%, 58%, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98% or 99%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] The positive electrode substrate material provided by the present invention uses medium-high nickel material, which is more conducive to the performance.

[0060] As a preferred technical solution in a specific embodiment, the chemical formula of the positive electrode matrix material is LiNi x Co y M 1-x-y O 2 , wherein M includes Mn and / or Al, x≥0.5, y≥0, 1-xy>0.

[0061] For example, the x can be 0.5, 0.53, 0.55, 0.58, 0.6, 0.63, 0.65, 0.68, 0.7, 0.73, 0.75, 0.78, 0.8, 0.83, 0.85, 0.88, 0.9, 0.93, 0.95, 0.98 or 0.99, etc.; the y can be 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48 or 0.49, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0062] As a preferred technical solution in a specific embodiment, the layered bimetallic oxide includes divalent metal elements and trivalent metal elements, and the positive electrode matrix material is also doped with the trivalent metal elements in the layered bimetallic oxide.

[0063] In the present invention, the trivalent metal elements in the layered bimetallic oxide can be further doped into the positive electrode matrix material to stabilize the internal structure of the material, and cooperate with the double-layer coating material and the coating sequence to play the triple role of increasing the diffusion channel, ion doping and surface modification, stabilizing the structure and interface, and simultaneously improving the electrical performance of the lithium-ion battery.

[0064] In another specific embodiment, the present invention provides a method for preparing the positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0065] first mixing the positive electrode matrix material and the lithium-rich disordered material, and performing a first sintering on the first mixed material to obtain an intermediate material;

[0066] The intermediate material and the layered double metal hydroxide material are mixed in a second manner, and the second mixed material is subjected to a second sintering to obtain the positive electrode material.

[0067] The preparation method provided by the present invention obtains an intermediate structure of a positive electrode matrix material coated with a lithium-rich disordered material through a first sintering, and a layered double hydroxide (LDHs) undergoes a second sintering, wherein the ordered layered structure of the LDHs is destroyed, the disorder is increased, and the hydroxide and carbonate ions are removed, and finally a layered double oxide LDO (containing only double metal and oxygen) with high stability and a large specific surface area is evolved, the pore radius becomes larger and more uniform, the amount of micropores increases, and it is more conducive to the deintercalation of lithium ions; thereby, a positive electrode material with a stable structure and excellent performance is obtained; the preparation method is simple to operate and does not require a complicated processing process.

[0068] As a preferred technical solution in another specific embodiment, the sintering temperature of the first sintering is 700°C~900°C, for example, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C, 875°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] As a preferred technical solution in another specific implementation, the sintering time of the first sintering is 4h~8h, for example 4h, 5h, 6h, 7h or 8h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] As a preferred technical solution in another specific embodiment, the sintering temperature of the second sintering is 400°C~650°C, for example 400°C, 425°C, 450°C, 475°C, 500°C, 525°C, 550°C, 575°C, 600°C, 625°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In the present invention, the sintering temperature of the second sintering is controlled to 400°C-650°C, and the LDH reaction to LDO is more thorough and complete, thereby obtaining an LDO material with a higher specific surface area and a larger pore volume; the electrochemical performance and thermal stability of the positive electrode material are further improved.

[0072] As a preferred technical solution in another specific implementation, the sintering time of the second sintering is 2h~4h, such as 2h, 3h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] As another preferred technical solution in another specific embodiment, the chemical formula of the layered double metal hydroxide is [A 2+ 1-x1 B 3+ x1 (OH) 2 ](C n- ) x1 / n ·zH 2 O, 0.2≤x1≤0.4, n>0, z>0.

[0074] For example, the x1 may be 0.2, 0.25, 0.3, 0.35 or 0.4, etc., the n may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc., and the z may be 1, 2, 3, 4, 5 or 6, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0075] Furthermore, A is a divalent metal element, and the divalent metal element includes at least one of Mg, Co, Ni, Zn or Cu.

[0076] The B is a trivalent metal element, and the trivalent metal element includes at least one of Al, Cr, Fe or Ga.

[0077] The C n- is an interlayer anion, wherein the interlayer anion includes NO - , Cl - OH - 、SO 4 2- ,PO 4 - , C 6 H 4 (COO) 2 2- At least one of .

[0078] In the present invention, Ni and Al with smaller ion radius are selected as divalent metal elements and trivalent metal elements. After the second sintering treatment, aluminum ions can enter the lattice of the positive electrode matrix material, play a role in ion doping, and stabilize the structure of the positive electrode material.

[0079] It should also be noted that the layered double metal hydroxide material provided by the present invention can be purchased directly or prepared by conventional preparation methods. Those skilled in the art can make adaptive selections and adjustments based on actual needs.

[0080] In one embodiment, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the positive electrode material as described in one of the above embodiments or the positive electrode material prepared by the preparation method as described in another of the above embodiments.

[0081] It should be noted that, except for the positive electrode material, the remaining structures, compositions and preparation methods of the lithium-ion battery provided by the present invention are conventional technical solutions, and those skilled in the art can select and adjust the specific types of lithium-ion batteries according to actual needs.

[0082] Specifically, the lithium-ion battery includes a liquid lithium-ion battery, a solid lithium-ion battery, a semi-solid lithium-ion battery, or the like.

[0083] The lithium-ion battery comprises a positive electrode, a negative electrode, an electrolyte and a separator (the separator is optional).

[0084] Among them, the negative electrode plate can be a lithium metal negative electrode, a pure negative electrode current collector negative electrode or a negative electrode structure including a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector; the negative electrode active material layer includes a negative electrode binder, a negative electrode active material and a negative electrode conductor.

[0085] Among them, the negative electrode binder includes but is not limited to polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc.; the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, silicon oxygen or silicon carbon. The negative electrode conductive agent includes at least one of conductive carbon black, carbon nanotubes, vapor-grown carbon nanotubes or nano-carbon fibers.

[0086] And, the main function of the separator is to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is a separator commonly used in lithium ion batteries. In particular, a separator with excellent electrolyte wettability and low resistance to ion movement in the electrolyte is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure with more than two layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.

[0087] In the present embodiment, the type of electrolyte is not particularly limited. Without violating the inventive concept of the present application, any known electrolyte material can be used in the present application. As an illustrative example, the electrolyte can be a liquid electrolyte, a solid electrolyte, or a mixed form of a solid electrolyte and a liquid electrolyte. In addition, the electrolyte used in the present invention can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used for the manufacture of a secondary battery, but is not limited thereto.

[0088] Specifically, the electrolyte may include an organic solvent and a lithium salt. Any organic solvent may be used without particular limitation, as long as it can act as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as an organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone may be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among the above-mentioned solvents, carbonate solvents are preferred, and a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ion conductivity and high dielectric constant and low viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) that can increase the charge / discharge performance of the battery is more preferred. In this case, when cyclic carbonates and chain carbonates are mixed with a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte may be excellent.

[0089] Any compound can be used as the lithium salt without particular limitation as long as it can provide lithium ions used in lithium secondary batteries. Specifically, LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F9SO 3 、LiN(C 2 F5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 、LiCl、LiI、LiB(C 2 O 4 ) 2 The lithium salt may be used in a concentration range of 0.1-2.0 mol / L. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby exhibiting excellent performance, and lithium ions can be efficiently moved.

[0090] As an embodiment, the electrolyte may be a solid electrolyte, and the solid electrolyte particles may include one or more polymer components, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, borate solid electrolytes, nitride solid electrolytes, or hydride solid electrolytes. When polymer particles are used, lithium salts should be used for compounding.

[0091] As a particular embodiment, the solid electrolyte may be a quasi-solid electrolyte comprising a mixture of the non-aqueous liquid electrolyte solution and the solid electrolyte system described in detail above, for example, comprising one or more ionic liquids and one or more metal oxide particles (such as aluminum oxide (Al 2 O 3 ) and / or silicon dioxide (SiO 2 )).

[0092] Exemplarily, the present invention provides a method for preparing a layered double metal hydroxide, the preparation method comprising:

[0093] The urea is uniformly dispersed in deionized water to obtain a dispersion, and the dispersion is added to an aqueous solution formed by 0.15 mol of a binary metal element salt, 0.05 mol of a ternary metal element salt and 0.8 mol of ammonium fluoride. The reaction is continued for 12 hours at a heating rate of ≤5°C / min under hydrothermal reaction conditions of 120°C. The reaction product is then repeatedly washed with deionized water and vacuum dried to obtain layered double hydroxides (LDHs) with good crystallinity.

[0094] The following examples and comparative examples all adopt the above-mentioned preparation method to prepare layered double metal hydroxides, and the specific element types can be adaptively selected and adjusted according to the specific substances in the examples.

[0095] Example 1

[0096] This embodiment provides a positive electrode material, which includes a core, a first coating layer and a second coating layer from the inside to the outside;

[0097] The core includes a positive electrode matrix material LiNi 0.8 Co 0.1 Mn 0.1 O 2 The first coating layer includes a lithium-rich disordered material Li having a rock salt structure and a D50 of 180 nm. 1.2 Mo 0.5 Cr 0.3 O 2 The mass of the first coating layer is 0.5% of the mass of the core; the second coating layer includes a layered bimetallic oxide NiAl-LDOs with a lamellar structure with a thickness of 20nm, and the mass of the second coating layer is 0.5% of the sum of the masses of the core and the first coating layer.

[0098] The preparation method of the positive electrode material is as follows:

[0099] The first step is to convert LiNi 0.8 Co 0.1 Mn 0.1 O 2 and Li 1.2 Mo 0.5 Cr 0.3 O 2 The mixed grinding was fully performed, the coating amount was 0.5%, the ball milling time was 5 h, the rotation speed was 350 r / min, and then the first sintering was performed, the sintering temperature was 800 ° C, the sintering time was 5 h, and the LiNi coated with the first coating layer was obtained by solid phase reaction. 0.8 Co 0.1 Mn 0.1 O 2 Electrode materials, i.e. intermediate materials;

[0100] In the second step, NiAl-LDHs with a coating amount of 0.5% was added to the anhydrous ethanol solution of the intermediate material, dispersed for 60 minutes, and then dried and subjected to a second sintering at a sintering temperature of 650°C for 3 hours to obtain the positive electrode material (NCM811@LMCO@NiAl-LDHs).

[0101] Figure 1 The XRD pattern of NiAl-LDHs provided in Example 1 is shown.

[0102] Figure 2 The XRD pattern of the positive electrode material provided in Example 1 is shown.

[0103] Figure 3 The SEM image of NiAl-LDHs provided in Example 1 is shown.

[0104] Figure 4 The positive electrode matrix material LiNi provided in Example 1 is shown 0.8 Co 0.1 Mn 0.1 O 2 SEM image of .

[0105] from Figure 1 It can be seen that the crystal planes of NiAl-LDHs prepared in the present invention in (003), (006), (009), (015), (018) and (110) match those of PDF#15-87, proving that the layered double hydroxide structure was successfully synthesized.

[0106] from Figure 2 It can be seen that the positive electrode material in the present invention is basically consistent with the standard card of NCM811, which indicates that the first coating layer and the second coating layer in the present invention do not significantly affect the crystal structure of the positive electrode matrix material, but the peak width and intensity of each characteristic peak change. (003) / I (104) The ratio increases slightly, indicating that the disordered site occupation ratio of Ni ions in the Li layer decreases, which is due to the Al ions in the coating layer entering the unit cell, further stabilizing the crystal structure.

[0107] from Figure 3 It can be seen that NiAl-LDHs presents a flower-like structure composed of many nanosheets. It can be clearly seen that these nanosheets are intertwined with each other to form a large number of open free space structures. This special structure has a large specific surface area.

[0108] from Figure 4 It can be seen that the uncoated positive electrode matrix material has a spherical shape, a smooth surface, and an average particle size of 10-15 μm.

[0109] Example 2

[0110] This embodiment provides a positive electrode material, which includes a core, a first coating layer and a second coating layer from the inside to the outside;

[0111] The core includes a positive electrode matrix material LiNi 0.8 Co 0.1 Mn 0.1 O 2 The first coating layer includes a lithium-rich disordered material Li having a rock salt structure and a D50 of 300 nm. 1.2 Mo 0.5 Cr 0.3 O 2The mass of the first coating layer is 1.5% of the mass of the core; the second coating layer includes a layered bimetallic oxide NiAl-LDOs with a lamellar structure with a thickness of 10nm, and the mass of the second coating layer is 2% of the sum of the masses of the core and the first coating layer.

[0112] The preparation method of the positive electrode material is as follows:

[0113] The first step is to convert LiNi 0.8 Co 0.1 Mn 0.1 O 2 and Li 1.2 Mo 0.5 Cr 0.3 O 2 The mixed grinding was fully performed, the coating amount was 1%, the ball milling time was 5h, the rotation speed was 350r / min, and then the first sintering was performed, the sintering temperature was 700℃, the sintering time was 8h, and the LiNi coated with the first coating layer was obtained by solid phase reaction. 0.8 Co 0.1 Mn 0.1 O 2 Electrode materials, i.e. intermediate materials;

[0114] In the second step, NiAl-LDHs with a coating amount of 2% is added to the anhydrous ethanol solution of the intermediate material, dispersed for 60 minutes, and then dried and subjected to a second sintering at a sintering temperature of 400° C. for 4 hours to obtain the positive electrode material.

[0115] Example 3

[0116] This embodiment provides a positive electrode material, which includes a core, a first coating layer and a second coating layer from the inside to the outside;

[0117] The core includes a positive electrode matrix material LiNi 0.6 Co 0.2 Mn 0.2 O 2 The first coating layer includes a lithium-rich disordered material Li having a rock salt structure and a D50 of 50 nm. 1.2 Mo 0.5 Cr 0.3 O 2 The mass of the first coating layer is 1% of the mass of the core; the second coating layer includes a layered bimetallic oxide NiAl-LDOs with a lamellar structure with a thickness of 2nm, and the mass of the second coating layer is 1.2% of the sum of the masses of the core and the first coating layer.

[0118] The preparation method of the positive electrode material is as follows:

[0119] The first step is to convert LiNi 0.8Co 0.1 Mn 0.1 O 2 and Li 1.2 Mo 0.5 Cr 0.3 O 2 The mixed grinding was fully performed, the coating amount was 1%, the ball milling time was 5h, the rotation speed was 350r / min, and then the first sintering was performed, the sintering temperature was 800℃, the sintering time was 5h, and the LiNi coated with the first coating layer was obtained by solid phase reaction. 0.8 Co 0.1 Mn 0.1 O 2 Electrode materials, i.e. intermediate materials;

[0120] In the second step, NiAl-LDHs with a coating amount of 1.2% is added to the anhydrous ethanol solution of the intermediate material, dispersed for 60 minutes, and then dried and subjected to a second sintering at a sintering temperature of 650° C. for 3 hours to obtain the positive electrode material.

[0121] Example 4

[0122] The difference between this embodiment and embodiment 1 is that the lithium-rich disordered material in this embodiment is Li 1.1 V 0.9 O 2 .

[0123] The rest of the preparation methods and parameters were the same as those in Example 1.

[0124] Example 5

[0125] The difference between this embodiment and embodiment 1 is that the bimetallics in the layered bimetallic oxide in this embodiment are Cu and Cr respectively.

[0126] The rest of the preparation methods and parameters were the same as those in Example 1.

[0127] Example 6

[0128] The difference between this embodiment and embodiment 1 is that the material in the first coating layer in this embodiment is a lithium-rich layered structure with a chemical formula of 0.3Li 2 MnO 3 ∙0.7LiNi 0.5 Mn 0.5 O 2 .

[0129] The rest of the preparation methods and parameters were the same as those in Example 1.

[0130] Example 7

[0131] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass of the first coating layer is 2% of the mass of the inner core, and the mass of the second coating layer is 2.5% of the sum of the masses of the inner core and the first coating layer.

[0132] The rest of the preparation methods and parameters were the same as those in Example 1.

[0133] Example 8

[0134] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass of the first coating layer is 2% of the mass of the core.

[0135] The rest of the preparation methods and parameters were the same as those in Example 1.

[0136] Example 9

[0137] The difference between this embodiment and embodiment 1 is that the mass of the second coating layer is 2.5% of the sum of the masses of the inner core and the first coating layer.

[0138] The rest of the preparation methods and parameters were the same as those in Example 1.

[0139] Example 10

[0140] The difference between this embodiment and embodiment 1 is that the thickness of the lamellar structure of the layered bimetallic oxide NiAl-LDOs in this embodiment is 30 nm.

[0141] The rest of the preparation methods and parameters were the same as those in Example 1.

[0142] Comparative Example 1

[0143] The difference between this comparative example and Example 1 is that the positive electrode material provided in this comparative example is a positive electrode base material, which does not contain a first coating layer or a second coating layer.

[0144] Comparative Example 2

[0145] The difference between this comparative example and Example 1 is that the positive electrode material provided in this comparative example does not contain the first coating layer.

[0146] In the preparation method, the first step of coating process is not carried out, and LiNi 0.8 Co 0.1 Mn 0.1 O 2 As an intermediate material mixed with NiAl-LDHs.

[0147] The rest of the preparation methods and parameters were the same as those in Example 1.

[0148] Comparative Example 3

[0149] The difference between this comparative example and Example 1 is that the positive electrode material provided in this comparative example does not contain a second coating layer.

[0150] In the preparation method, the second step of the preparation process is not carried out.

[0151] The rest of the preparation methods and parameters were the same as those in Example 1.

[0152] Comparative Example 4

[0153] The difference between this comparative example and Example 1 is that in the positive electrode material provided in this comparative example, the coating materials of the first coating layer and the second coating layer are interchanged.

[0154] Just make adaptive adjustments in the preparation method.

[0155] The rest of the preparation methods and parameters were the same as those in Example 1.

[0156] The positive electrode materials provided in Examples 1-10 and Comparative Examples 1-4 are used to prepare a battery structure.

[0157] Battery preparation:

[0158] Preparation of positive electrode plate: prepare positive electrode slurry according to the ratio of positive electrode material: SP: PVDF = 8:1:1 to obtain single crystal positive electrode slurry for use, wherein the slurry solid content is 60%; place aluminum foil on a coater, use a 150μm coater to place it on the aluminum foil, pour the slurry, start the equipment for coating, and obtain the electrode plate after coating. Place the electrode plate in a 110°C oven for drying and roll-press to obtain the positive electrode plate.

[0159] The positive electrode sheets provided were cut into discs with a diameter of 15 mm in a dry environment by a punching machine. A metal lithium sheet was used as a counter electrode in a glove box. A polypropylene PP diaphragm was selected as an isolation membrane. An electrolyte was added to assemble a button cell. The electrolyte was an organic solution obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a mass ratio of 30:50:20. The concentration of lithium salt (lithium hexafluorophosphate) in the electrolyte was 1.15 mol / L.

[0160] Performance Testing:

[0161] (a) The positive electrode sheets provided in Examples 1-10 and Comparative Examples 1-4 were respectively cut, and then a pressure of 100 MPa was applied, and the pressure was maintained for 10 seconds to test the conductivity of the electrode sheets.

[0162] (2) The performance tests of the button batteries provided in Examples 1-10 and Comparative Examples 1-4 were performed using the Wuhan Blue Power CT2001A system:

[0163] a) Electrochemical performance test: The button cell was charged to 4.3V using constant current-constant voltage, with a cut-off current of 0.05C in the constant voltage stage, and then discharged to 2.8V using constant current, including currents of 0.2C, 1C and 5C.

[0164] b) Thermal stability test: The button cell was discharged to 2.5 V, and then the positive electrode was taken out of the glove box and immersed in the DMC solution for 30 min. Then a differential scanning calorimetry (DSC) test was performed. During the test, the electrolyte was added at a mass ratio of 2:1 to the positive electrode. After the test, the exothermic peak starting temperature and thermal enthalpy value of the positive electrode were obtained.

[0165] The criteria for high thermal stability are: the exothermic starting temperature is 240°C and above, and the thermal enthalpy value is lower than 200J / g; the criteria for medium thermal stability are: under the premise of not meeting the high thermal stability, the exothermic starting temperature is 220°C and above, and the thermal enthalpy value is lower than 350J / g; the criteria for low thermal stability are: not meeting the exothermic starting temperature and thermal enthalpy value of high thermal stability and thermal stability.

[0166] The test results of the above tests are shown in Table 1.

[0167] Table 1

[0168]

[0169] In summary, the positive electrode material provided by the present invention, the coating materials of the first coating layer and the second coating layer, and the coating sequence cooperate with each other to jointly coat and modify the positive electrode matrix material, which can achieve rapid lithium ion deintercalation. The lithium-rich disordered material in the first coating layer has a high lithium threshold and can form a percolation network, open a new ion migration channel 0-TM, accelerate migration and diffusion, improve rate performance, and can also reduce the surface alkali content and stable structure of the positive electrode matrix material; the layered bimetallic oxide in the second coating layer provides a large amount of open space, which increases the specific surface area of ​​the material while providing surface protection, can absorb part of the oxygen released by the positive electrode, improve the thermal stability of the positive electrode material, reduce the internal resistance of the battery, and inhibit the dissolution of the electrode material and the cracking of the secondary particle surface; at the same time, the double-layer coating makes the material exhibit good chemical corrosion resistance, and reduces the problems of agglomeration and sintering of nanoparticles, thereby improving the thermal stability, rate performance and cycle performance of the positive electrode material.

[0170] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes a core, a first coating layer and a second coating layer from the inside to the outside; The core includes a positive electrode matrix material; the first coating layer includes a lithium-rich disordered material; the second coating layer includes a layered bimetallic oxide; the lithium-rich disordered material is a rock salt structure material; the chemical formula of the lithium-rich disordered material is Li a TM 2-a O2, 1≤a<2, TM is a transition metal element.

2. The positive electrode material according to claim 1, characterized in that The first coating layer satisfies at least one of the following conditions (c) to (d): (c) the D50 of the lithium-rich disordered material is 50 nm to 300 nm; (d) The mass of the first coating layer is 0.5% to 1.5% of the mass of the core.

3. The positive electrode material according to claim 1, characterized in that The second coating layer satisfies at least one of the following conditions (e) to (g); (e) the layered bimetallic oxide has a lamellar structure, and the thickness of the lamellar structure is 2 nm to 20 nm; (f) the layered bimetallic oxide comprises a divalent metal element A and a trivalent metal element B, wherein the divalent metal element A comprises at least one of Mg, Co, Ni, Zn or Cu, and the trivalent metal element B comprises at least one of Al, Cr, Fe or Ga; (g) The mass of the second coating layer is 0.5% to 2% of the sum of the mass of the core and the first coating layer.

4. The positive electrode material according to claim 1, characterized in that Taking the total molar amount of all metal elements in the positive electrode matrix material as 100%, the molar amount of nickel in the positive electrode matrix material accounts for ≥50%.

5. The positive electrode material according to claim 4, characterized in that The chemical formula of the positive electrode matrix material is LiNi x Co y M 1-x-y O2, wherein M includes Mn and / or Al, x≥0.5, y≥0, 1-xy>0.

6. The positive electrode material according to claim 4 or 5, characterized in that The layered bimetallic oxide includes divalent metal elements and trivalent metal elements, and the positive electrode matrix material is also doped with the trivalent metal elements in the layered bimetallic oxide.

7. A method for preparing a positive electrode material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: first mixing the positive electrode matrix material and the lithium-rich disordered material, and performing a first sintering on the first mixed material to obtain an intermediate material; The intermediate material and the layered double metal hydroxide material are mixed in a second manner, and the second mixed material is subjected to a second sintering to obtain the positive electrode material.

8. The preparation method according to claim 7, characterized in that: The sintering temperature of the first sintering is 700° C. to 900° C., and the sintering time of the first sintering is 4 h to 8 h; and / or, The sintering temperature of the second sintering is 400° C. to 650° C., and the sintering time of the second sintering is 2 h to 4 h.

9. The preparation method according to claim 7, characterized in that: The chemical formula of the layered double metal hydroxide is [A 2+ 1-x1 B 3+ x1 (OH)2] (C n- ) x1 / n zH2O, 0.2≤x1≤0.4, n>0, z>0, wherein the chemical formula satisfies the following conditions (h) to (j); (h) A is a divalent metal element, and the divalent metal element includes at least one of Mg, Co, Ni, Zn or Cu; (i) B is a trivalent metal element, and the trivalent metal element includes at least one of Al, Cr, Fe or Ga; (j) C n- is an interlayer anion, wherein the interlayer anion includes NO3 - , Cl - OH - 、SO4 2- PO4 - 、C6H4 (COO)2 2- At least one of .

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Lithium ion battery ternary material with double-coated surface and preparation method thereof

    CN107768642A

  • High-nickel positive electrode material and preparation method and application thereof

    CN112635756A

  • Positive electrode active material and preparation method thereof, positive electrode plate and lithium ion battery

    CN117525411A